Screening Phosphorylation Site Mutations in Yeast Acetyl-CoA Carboxylase Using Malonyl-CoA Sensor to Improve Malonyl-CoA-Derived Product - Chen, Xiaoxu; Yang, Xiaoyu; Shen, Yu; Hou, Jin; Bao, Xiaoming (Frontiers in Microbiology, 2018)
Malonyl-CoA is a critical precursor for the biosynthesis of a variety of biochemicals. It is synthesized by the catalysis of acetyl-CoA carboxylase (Acc1p), which was demonstrated to be deactivated by the phosphorylation of Snf1 protein kinase in yeast. In this study, we designed a synthetic malonyl-CoA biosensor and used it to screen phosphorylation site mutations of Acc1p in S. cerevisiae. Thirteen phosphorylation sites were mutated, and a combination of three site mutations in Acc1p, S686A, S659A, and S1157A, was found to increase malonyl-CoA availability. ACC1S686AS659AS1157A expression also improved the production of 3-hydroxypropionic acid, a malonyl-CoA-derived chemical, compared to both wild type and the previously reported ACC1S659AS1157A mutation. This mutation will also be beneficial for other malonyl-CoA-derived products.